The reinforcement of the national dimension as an argumentative mechanism in political discourse The discourse of the four political parties in the Kurdistan Region, for example - جراد, د. چۆلی اسعد (Sulaimani Journal for Humanities, 2025)
This study (Repetition of The ethnic Dimension as an Argumentation Mechanism in Political Discourse (the Discourse of the Four Political Parties in the Kurdistan Region for example)) works through statistical analysis to identify the repetitions that have an ethnic dimension in the discourse of political parties used, especially in oral political discourses are directed. Because repetition generally plays an argumentative role in political discourse and is used to influence and persuade, However, when the affirmation takes on an ethnic dimension in political discourse, it can be more effective. Language and rhetoric do not find themselves solely in conveying meaning and understanding. Instead, the sender must combine his or her way of expressing his or her intention, As is well known, expressive language and rhetoric are not only used for pleasure but also creative and persuasive effects. Repetition of The ethnic Dimension is considered one of the most obvious of these methods. In this study, relying on the discourse analysis theory, attention was paid to identifying the recurrence of ethnic dimensions of discourses in the samples taken. In this study, relying on the grounded theory of discourse analysis, attention was paid to identifying the reinforcement of the ethnic dimensions of the sampled discourses. In political discourse, the affirmation of the ethnic dimension as a mechanism of linguistic argument also sees the function of influence and persuasion.
Keywords: Political discourse; argumentation; argumentative mechanisms; national dimension